Traditional and local use of medicinal plants by local communities in Hezar Jerib summer area, north of Iran - Isa Jafari Footami; Moosa Akbarlou (Journal of Herbal Drugs, 2017)
Background & Aim: Some knowledge about medicinal plants is available in old references or books. But important point is the information of traditional usage of medicinal plants from different parts of Iran will be worthwhile and in addition to encouraging people to it provides a good background for future examination about medicinal plants.The objectives of this study is to identify the medicinal plants along with local names, utilized parts, administration route, ailments treated, therapeutic effect and preparation methods. Experimental: So to get this information, we use semi-structured interviews. This research was conducted in the summer and spring of 2016. During this period around 150 individuals (75 men, 75 women; in an age group between 20 and 95 years) were interviewed in 6 villages. Number of questions in this survey was 15 questions. Ethno botanical data were analyzed by use-reports. In addition important indices like Informant Agreement Ratio (IAR), Relative Frequency of Citation (RFC) and Cultural Importance (CI) were calculated. Furthermore, a traditional null hypothesis testing was adopted. These are the most popular indices in quantitative ethno botany. Results: A total of 54 medicinal plants belonging to 22 families were identified. The most common families are Lamiaceae, Asteraceae, Apiaceae and Rosaceae, with 22, 17, 5 and 4%, respectively. The most common preparations methods were infusion (52%), eaten raw and decoction (13%). Also, between different parts of the plant, the leaves are mostly used. According to RFC and CI indices, the most important plant is Gallium verum. Nervous disease has the highest Informant Consensus Factor value with the rate of 0.80. Recommended applications/industries: Introduction of medicinal plants in each region, along with their use can be a great help to create jobs and Encouraging people to cultivate these plants.